ESTIMATION OF FRACTURE RESISTANCE OF NANOCOMPOSITE FILLING MATERIALS USING ACOUSTIC EMISSION METHOD - Kukhta, V.S.; Kyrmanov, O.S.; Makeyev, V.F.; Stankevych, O.M. (World of Medicine and Biology, 2022)
The strength characteristics and features of the fracture of nanocomposite filling materials under bending using the acoustic emission method were analyzed. Nanocomposites are one of the widely used filling materials. To ensure the long-term operation of such restorations, it is important to know the dynamics of the fracture propagation in them under the influence of load. Four commercial nanocomposites were ranked by flexural strength, and modulus of elasticity using the acoustic emission method. Their fracture resistance was estimated by the analysis of acoustic emission signal parameters. Based on a matrix with triethylene glycol dimethacrylate monomer nanocomposite from a foreign manufacturer has the highest flexural strength (164.44±20.42 MPa) and resistance to fracture. Based on a matrix with ethoxylated bisphenol-A dimethacrylate monomer composite has the highest modulus of elasticity (107.46±2.95 GPa). The results of the performed studies will help to make an effective choice of filling materials to ensure the long-term operation of the corresponding restorations.
Keywords: dental restorative materials; nanocomposite; fracture strength; composite resin; acoustic emission